The Importance of Sex in the Lives of Women Living with HIV: A Critical Quantitative Analysis. Issue 1 (2nd January 2018) - Carter, Allison; Greene, Saara; Money, Deborah; Sanchez, Margarite; Webster, Kath; Nicholson, Valerie; Brotto, Lori A.; Hankins, Catherine; Kestler, Mary; Pick, Neora; Salters, Kate; Proulx-Boucher, Karène; et al.
ABSTRACT: The authors explored the importance of sex for 1, 289 women living with HIV in Canada. Approximately half of women viewed sex as "very" (19.6%) or "somewhat" important (32.3%) and the remaining reported "neither important or unimportant" (22.0%), "somewhat unimportant" (5.4%), or "not at all important" (20.1%). Women who had a regular sex partner, identified as African, Caribbean, or Black, were more educated, believed HIV treatment prevents transmission, or had better physical health-related quality-of-life reported greater importance of sex, whereas those who were older, used illicit drugs, or experienced violence in adulthood reported lesser importance. Findings underscore the diversity of women's perspectives within the context of their lives.